Knowledge, attitude, and perception of Pakistani populations toward monkeypox: a cross-section study - Yousaf, Humayun; Qadeer, Abdul; Sohail, Muhammad; Khan, Maqbool; Farooq, Muhammad; Khan, Zakir; Fouad, Dalia; Liu, Yu-Chia; Chen, Chien-Chin (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThe reappearance of monkeypox in non-endemic countries has preceded critical public health concerns. The public’s adherence to preventative measures is influenced by their understanding of the infectious monkeypox virus (Mpox), attitude toward it, and perceptions of it. We conducted this study to evaluate the general population’s knowledge, attitude, and perceptions of Mpox in Pakistan.MethodsFrom August 15 to August 30, 2022, 3465 participants in this cross-sectional study provided information via an online survey. The survey has 37 questions divided into four categories: sociodemographic, knowledge, attitude, and perceptions of Mpox. Statistical analyses were performed in Jupyter Notebook using Python 3 and the Pandas, Matplotlib, and stats libraries.ResultsThe chi-square test and regression analysis evaluated factors related to Mpox knowledge, attitude, and perception of three thousand four hundred sixty-five participants. Among the participants, about 79.51% (2755) were male, and 32.99% (1143) had post-graduation level education. About 521(99.24) participants with post-graduation education have positive knowledge with a p-value of 0.0001. Approximately 66.78% (2314) of participants answered that Mpox is prevalent in African countries. Almost 85.69% (2969) stated that a virus causes Mpox, and more than 72.18% (2501) said that Mpox spreads through contaminated surfaces. About 60.52% (2097) of participants answered that antivirals are required in treating Mpox patients. Around more than half of the participants, 52.64% (1824), believe that those who receive the chickenpox vaccination are protected against Mpox. It’s interesting to note that most research participants felt favorably about Mpox. Around 90.22% (3126) of participants believed Mpox would be effectively eradicated. Most participants, 86.7% (3004), believe that people should care more about one another nowadays, and 81.36% (2819) believe visiting areas with a Mpox outbreak is risky. About 83.95% (2909) answered that during interaction with the Mpox patient, they’d dress in the appropriate personal protective clothing, like masks, gloves, and gowns. At the same time, 77.66% (2691) responded that they would perform hand hygiene after touching the patients’ surroundings, like beds, tables, doors, etc.ConclusionsMaximum research participants showed good attitudes and knowledge about Mpox. However, it is essential to start and execute a planned planning framework for public health awareness to avoid the occurrence and spread of Mpox in Pakistan.